DPWH Region Eight Employees Multi-Purpose Cooperative (DREEMC) Focusing on participation, liberty, empowerment and progress. - Lucero, Lucie Antonette D. (Tacloban City Lucie Antonette D. Lucero, 2009)
Cooperatives are people organizations. They are organized to serve people's needs either by increasing their economic income or by providing products and services not available from other sectors of the business community. The purpose of this study is to determine the level of democratization and development in the DPWH Region Eight Employees Multi-Purpose Cooperative (DREEMC) through the following variables: political participation, political liberty, empowerment and progress. I engage myself into interviewing some of the officials and members to know their experiences with the Cooperative. Important facts were also taken from the Cooperative's By-Laws and Article of Cooperation. This study examines how democratization works in the DREEMC through the said variables. Results from these suggest that the DREEMC is forwarding democratization and advancing development to its members and to the Cooperative.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban.
Keywords: Social Science